Is there a need to widely prescribe antibiotics in patients hospitalized with COVID-19?. (April 2021) - Moretto, F.; Sixt, T.; Devilliers, H.; Abdallahoui, M.; Eberl, I.; Rogier, T.; Buisson, M.; Chavanet, P.; Duong, M.; Esteve, C.; Mahy, S.; Salmon-Rousseau, A.; et al.
Highlights: Antibiotics were prescribed to may patients with coronavirus disease 2019 during the first wave of the pandemic. Bacterial co-infection seems to be rare, especially in patients who do not require transfer to an intensive care unit. This study investigated the role of antibiotic therapy and its impact on prognosis. Patients with more severe infection were often prescribed antibiotic therapy, but this had no impact on prognosis. Antibiotic therapy should not be widely prescribed. Abstract: Background: Debate continues regarding the usefulness and benefits of wide prescription of antibiotics in patients hospitalized with coronavirus disease 2019 (COVID-19). Methods: All patients hospitalized in the Infectious Diseases Department, Dijon University Hospital, Dijon, France between 27 February and 30 April 2020 with confirmed COVID-19 were included in this study. Clinical, biological and radiological data were collected, as well as treatment and outcome data. An unfavourable outcome was defined as death or transfer to the intensive care unit. Patient characteristics and outcomes were compared between patients who did and did not receive antibiotic therapy using propensity score matching. Findings: Among the 222 patients included, 174 (78%) received antibiotic therapy. The univariate analysis showed that patients who received antibiotic therapy were significantly older, frailer and had more severe presentation at admission compared with patients who did not receive antibiotic therapy. Unfavourable outcomes were more common in patients who received antibiotic therapy [hazard ratio (HR) 2.94, 95% confidence interval (CI) 1.07–8.11; P = 0.04]. Multi-variate analysis and propensity score matching indicated that antibiotic therapy was not significantly associated with outcome (HR 1.612, 95% CI 0.562–4.629; P = 0.37). Conclusion: Antibiotics were frequently prescribed in this study and this was associated with more severe presentation at admission. However, antibiotic therapy was not associated with outcome, even after adjustment. In line with recent publications, such data support the need to streamline antibiotic therapy in patients with COVID-19.